On the Cauchy Functional Inequality in Banach Modules - Choonkil Park (Journal of Inequalities and Applications, 2008)
We investigate the following functional inequality: ‖f(x)+f(y)+f(z)‖≤‖f(x+y+z)‖ in Banach modules over a C∗-algebra, and prove the generalized Hyers-Ulam stability of linear mappings in Banach modules over a C∗-algebra.